Analysis of Electric Motor Cooling and Heating - E.E.Abdurashidov; B. R.Yuldashev (European Science Publishing, 2023)
The cooling method of an electric motor is too complex to accurately predict the heat flow and temperature distribution. A part of the conductors of the armature winding is installed in the slots and a part is outside the steel material. Heating calculations are also complicated by engine loading. The direction of heat flow does not remain the same under all loading conditions. Under no-load or lightly loaded conditions, heat flows from the steel parts to the winding due to the temperature gradient. Once the load is increased, the gradient changes because the heat generated (loss) in the winding is greater than the heat generated (loss) in the steel parts, and as a result heat flows from the winding to the metal surface. Therefore, a significant simplification is needed to calculate the temperature rise of the engine.
Keywords: heating,cooling, power loss, cooling surface,cooling methods, heat balance.